Protein expression and antifungal effect of fluconazole-resistant Candida species following effective in vitro treatment with K21, a novel antifungal agent - John, Cathy Nisha (University of Western Cape, 2021)
Philosophiae Doctor - PhD === Background: Oropharyngeal candidiasis, caused by the fungus Candida, is the most common opportunistic infection affecting the quality of life of immunocompromised patients. Fluconazole is widely used as the first line of treatment for fungal infections. However, the inappropriate and misguided use of the drug has led to the evolvement of fluconazole-resistant Candida organisms. This arising resistance resulted in the urgent need for the development of new antimicrobial drugs. The aim of the present study was to investigate the antifungal action of K21, a novel antimicrobial quarternary ammonium compound, on fluconazole-resistant Candida species.